2008
DOI: 10.1038/sj.bjc.6604282
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors and treatment effects for hepatocellular carcinoma in Child C cirrhosis

Abstract: The aim of this study is to elucidate the prognostic factors and the treatment effect on survival in hepatocellular carcinoma (HCC) patients with Child C cirrhosis. Out of 3330 newly discovered HCC patients, 157 consecutive HCC individuals with Child C cirrhosis were enrolled. The prognostic factors were examined by Cox proportional hazards regression analysis and their survival was compared by propensity score-matched analysis. Multivariate analysis revealed that high serum bilirubin (43 mg dl À1 ), the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 24 publications
1
40
0
1
Order By: Relevance
“…Despite the poor prognosis of Child-Pugh C disease, the present results show that treatment might improve prognosis in patients with low Child-Pugh scores, which is in agreement with the results reported by Nouso et al [15]. …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Despite the poor prognosis of Child-Pugh C disease, the present results show that treatment might improve prognosis in patients with low Child-Pugh scores, which is in agreement with the results reported by Nouso et al [15]. …”
Section: Discussionsupporting
confidence: 83%
“…This may be attributed to the frequent use of superselective TACE even in multinodular HCC patients in Japan, which does not cause deterioration of liver function. A previous report also described that superselective TACE was identified as having survival benefit in HCC patients with Child-Pugh C [15]. …”
Section: Discussionmentioning
confidence: 99%
“…Nouso et al [19] reported that RFA had no effects on the prognosis of patients with Child-Pugh C liver cirrhosis. However, our data showed that the survival rate after 1 year in Child-Pugh C patients with HCC was 68.0%.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of the treatment modality depends on the number of tumors and their size, the stage and the cause of cirrhosis and the availability of various modalities in each center [7]. The effect of different associated risk factors including number, size and location of tumor, serum alpha fetoprotein level, portal involvement, vascularity and Child-Pugh score have been previously studied [11,12,29,30]. These studies have also evaluated the response of males compared with females [12,29].…”
Section: Discussionmentioning
confidence: 99%
“…Although the effect of associated risk factors including the number and location of lesions, tumor size, ChildPugh score, vascularity, portal involvement and alpha fetoprotein value on tumor response using TACE have already been studied [10][11][12], the effect of CLD using multivariate logistic analysis of associated risk factors is still unclear. The aim of this study is to evaluate the effect of CLD on tumor response in HCC patients treated with TACE using multivariate regression model while regarding associated risk factor analysis.…”
Section: Introductionmentioning
confidence: 99%